Las nuevas formas de la guerra y el cuerpo de las mujeres - Segato, Rita Laura (2014)
New wars, characterized by informality, unfold today in a liminal space that can be defined as parastatal because is controlled by armed corporations with the participation of state and non-state military personnel. In that expanding sphere of parastatality, violence against women is not a collateral damage of war any more but it has become a strategic objective of this new war scenario. This article examines the historical transformations around the informalization of war and points at the centrality obtained by a "pedagogy of cruelty" against those who do not play the role of armed antagonists in the fighting - women and children.